Tracing and archiving 'constructed' data on Facebook pages and groups: reflections on fieldwork among young activists in Zimbabwe and South Africa. (December 2017) - Mare, Admire
This study triangulates offline and online research methods to examine how and why young activists in Zimbabwe and South Africa use Facebook for political purposes. It demonstrates that like traditional participant observation, which was popularized by classical anthropologists, algorithmically 'occurring' data gathered through social media ethnography provides some of the richest information to burrow into the everyday political lives of young activists (who are generally presented in mainstream literature as having disengaged from traditional forms of political participation). Building on Postill and Pink's (2012) typology of social media ethnography, this study proposes a seven stage criteria for conducting online participant observation on Facebook in the era of data 'deluge'. These stages include: background listening, friending/liking, interacting, observing, catching up, exploring, and archiving. Based on the author's multi-sited fieldwork experiences in Zimbabwe and South Africa, this study argues that online like offline participant observation has context specific methodological dilemmas which require innovative flexibility and ethical sensitivity on the part of the qualitative researcher. It also discusses various ethical dilemmas which the author encountered during the multi-sited fieldwork as well practical strategies other researchers can use for delurking, archiving and safeguarding participants' privacy and confidentiality.